ISSUES OF IMPROVING PROSECUTOR’S SUPERVISION OVER LEGISLATIVE IMPLEMENTATION IN THE FIELD OF ENVIRONMENTAL PROTECTION - Arzikulov Adham Alimardon ugli (Scholar Express Journals, 2023)
this article covers the legal framework for ensuring prosecutorial supervision over the protection of the environment and the tasks of the prosecutor’s office, the bodies carrying out the protection of the environment in Uzbekistan, the current state of environmental protection and the problems and threats facing this area, as well as the issues of solving the tasks facing the state in this area.
Keywords: prosecutor’s supervision; specialized prosecutor’s office; Environmental Protection